How does gamification engage public school students? - SILVA, Denilson Deoclides da (2023)
The objective of this research is to investigate and analyze the gamification process, using video game elements as a pedagogical tool in non-gaming situations, as a motivational teaching tool, that can assist in learning and in general teaching development. It can be observed that even with the rise in popularity and quantity of technology in addition to the quality of games and digital resources, we still find resistance in terms of jobs, these technical resources are used as tools to assist learning. Therefore, studying the insertion of these resources in classroom practice is important for assessing students’ interests and potential. This work aims to list multiple concepts of gamification and its advantages and disadvantages, analyze neuroscience as a form of entertainment and learning, identify through the use of games and technical resources, and how students use them. The choice of the bibliography is based on the works that can answer the concerns that the subject aroused because many were them and through them, it was possible to gather essential data in the understanding of this subject.